Pengaruh Brand Attachment Terhadap Customer Engagement dengan Brand Trust Sebagai Variabel Mediasi dalam Perspektif Manajemen Bisnis Syariah - Indico Yudha Ardhana; Erike Anggraeni; Zathu Restie Utamie (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Brand attachment is a condition where consumers feel that the brand of a product represents and binds them in the sense that when the brand requires a constructive response, consumers will spontaneously provide and provide a positive response because of the experience they feel. This experience then makes consumers feel the need to be involved in developing the brand by being loyal to the brand and that loyalty makes trust in the brand maintained. The population in this study is the Way Kandis Community, Tanjung Senang District with the criteria that have been determined. The number of samples was 100 respondents. This research method is quantitative with online questionnaire data collection techniques through google form with the analysis method using a structural equation model approach with the SmartPLS 4 application. The results showed the results of Brand Attachment have a positive and significant effect on Customer Engagement, Brand Attachment has a positive and significant effect on Brand Trust, Brand Trust has a positive and significant effect on Customer Engagement, Brand Attachment has a positive and significant effect on Customer Engagement mediated by Brand Trust.